The stock market effects of a securities transaction tax: quasi-experimental evidence from Italy - Giuseppe Cappelletti; Giovanni Guazzarotti; Pietro Tommasino (European Central Bank (ECB), 2016)
We study the effects on the stock market of a securities transaction tax (STT). In particular, we focus on the recent introduction of a STT in Italy. Indeed, a peculiarity of the Italian STT is that it only concerns stocks of corporations with a market capitalization above 500 million euros. We exploit this feature via a differences-in-differences approach (comparing taxed and non-taxed stocks both before and after the introduction of the new tax). We find that the new tax widened the bid-ask spread and increased volatility, while it left transaction volumes and returns substantially unaffected. Results are broadly similar using a regression discontinuity design, in which we confront the performance of stocks just above the threshold with those just below.
Keywords: G14; G18; H24; 330; market liquidity; market volatility; securities transaction tax